Infographic. Tramadol: should it be banned in athletes while competing, particularly in road cycling? - Baltazar-Martins, Joao Gabriel; Plata, María del Mar; Muñoz-Guerra, Jesús; Muñoz, Gloria; Carreras, Daniel; Del Coso, Juan (British journal of sports medicine, 2020)
In the past years, tramadol has caught attention of media and antidoping authorities because this substance might be the subject of abuse in some sports, notably cycling.2 WADA determined that the use of some narcotics are prohibited in-competition but tramadol has never been banned, and it has not been included in the 2019 Prohibited List.3 Nevertheless, WADA has been monitoring the abuse of tramadol in all sports through the assessment of urine tramadol concentration in the samples obtained in-competition. Unlike WADA, the UCI will obtain in-competition blood samples, and positive results will depend on the presence of the substance in the blood at any quantity.5 The current infographic presents information about the 2017 WADA Monitoring Program.6 Specifically, the distribution of tramadol findings in 122 706 urine samples obtained in-competition. Since WADA’s main objective is to guarantee the safety and equality of all athletes, it becomes imperative to provide evidence that clarifies the clinical benefits of tramadol in sport setting, the possible ergogenic effects in competition and the drawbacks derived from acute and chronic ingestion of this opioid.